Psychological and physical impact of the haze amongst a Malaysian Community - Teoh Hsien-Jin,; Tan, Kai Ling (Penerbit UKM, 2008)
A total of 306 Malaysian university students and staff were surveyed to ascertain the physical and emotional effects of the polluted haze on them. All subjects completed self-reported questionnaires. Analysis of the results indicated that the majority of subjects reduced their outdoor activities and sports, and also reported an increase in emotional and physical health problems. The results indicated that there was a general increase in emotional problems such as feeling depressed, lacking in energy, not feeling like doing anything, feeling anxious and afraid, difficulty sleeping, feeling agitated and irritable, and having no appetite. There was also an increase in physical symptoms such as itchy or red eyes, itchy or running nose, dry throat/cough,headaches, nausea, and fever. This study indicated that emotional and behavioural problems are just as common during the haze, when compared with physical health problems. The study also suggests that there are a broad range of problems which health care and human resource departments need to be aware of and take precautions to minimize during a haze.